Pengaruh Lama Waktu Steaming dan Tiris terhadap Warna Seduhan Teh Hijau dengan Variasi Media Penyeduh - Diva Octavian; Ngatirah; Hilman Maulana (Program Studi Teknologi Hasil Pertanian, 2024)
There were two methods of green tea processing, namely the panning method and the steaming method. The panning method often produces unstable quality of tea because temperature and pressure of the heat on the process are not evenly distributed, so that green tea becomes burnt, or the polyphenol oxidase enzyme not inactivated as well. Therefore, green tea processing was developed using the steaming method. This research aimed to determine the effect of steaming time and draining time on the color of green tea brewed water with different brewing media. This study used the Randomized Complete Complete Block Design (RCBD) method with 2 factors. The first factor is length of steaming time with 3 levels, there are 2 minutes, 3,5 minutes and 5 minutes. The second factor is length of draining time with 3 levels, 0 hours, 2 hours and 4 hours. The results showed that steaming time had a significant effect on the G, B, L* and ∆E values of the brewed water color with Le Minerale. However, it didn’t significantly affect the R value with Le Minerale, the R, G, B, L* and ∆E values with distilled water and Gambung water. The draining time significantly affected the R, G, B, L* and ∆E values of the brewed water color with Le Minerale, as well as the G, L* and ∆E values with Gambung water. However, it did not significantly affect the R, G, B, L* and ∆E values with distilled water, the R and B values with Gambung water.